Assessment of trypanosome prevalence in FITCA high risk areas - Fyfe. K.; Picozzi, K.; Fèvre, Eric M.; Wasiwa, C.; McDermott, John J.; Welburn, S.C. (2003)
Currently in Southeast Uganda, FITCA (EU funded Farming in Tsetse Controlled Areas Project) is involved in an intervention programme against both animal trypanosomiasis and human sleeping sickness. This is a regional project involving Kenya, Ethiopia, Tanzania and Uganda. In southeast Uganda, the project first carried out livestock surveys and then a risk assessment for trypanosomiasis. Each sub-country in the FITCA area was graded as high, medium, low or no risk. High risk areas for sleeping sickness were identified by taking into account any cases of human sleeping sickness coupled with a survey of cattle in each district, identifying trypanosome species and prevalence microscopically. In areas deemed to be high risk, FITCA undertook to treat all of the cattle with a single dose of the trypanocide isometamidium chloride. This study aims to assess the prevalence of trypanosome infection in these FITCA high risk areas by PCR